1908 Md. Laws 79 - (:unkn) unknown (My University, 1908)
§ 32A: That any person who breaks and enters, either by day or by night, any building, whether inhabited or not, and opens or attempts to open any vault, safe or other secure place by the use of nitroglycerine, dynamite, gunpowder or other explosive, shall be deemed guilty of burglary with explosives.
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME